3-Fluorophenmetrazine, a fluorinated analogue of phenmetrazine: Studies on in vivo metabolism in rat and human, in vitro metabolism in human CYP isoenzymes and microbial biotransformation in Pseudomonas Putida and wastewater using GC and LC coupled to (HR)-MS techniques - Mardal, Marie; Meyer, Markus Robert (Journal of pharmaceutical and biomedical analysis, 2016)
Wastewater-based epidemiology (WBE) as means to estimate illicit drug and new psychoactive substance (NPS) consumption with spatial and temporal resolution is gaining increasing attention. In order to evaluate a given NPS using WBE, in vivo metabolism and microbial biotransformation of excretion products and unchanged compounds need evaluation. The aims of this study were to identify in vivo phase I and II metabolites of the NPS 3-fluorophenmetrazine (3-FPM) in human and rat urine and study the in vitro contribution of Cytochrome P450 (CYP) isoenzymes in phase I metabolism. Additionally, to study microbial biotransformation products (MBPs) of 3-FPM from incubations in wastewater and in a wastewater isolated Pseudomonas Putida strain. To these aims gas chromatography and liquid chromatography coupled to mass spectrometry were applied. Metabolites and MBPs were isolated from urine and microbial incubations after solid phase extraction and precipitation with or without enzymatic conjungate cleaving. The main transformation pathways were N-oxidation, aryl hydroxylation and subsequent O-methylation, alkyl hydroxylation, oxidation, and degradation of the ethyl-bridge yielding the O/N-bis-dealkylated metabolite, combinations thereof and further glucuronidation or sulfations. The main excretion products in the human urine sample were the unchanged compound and the N-oxide, and the main MBPs were the N-oxide and hydroxylation with subsequent oxidations on the alpha-methyl position. Based on these findings, the proposed strategy for WBE analysis of 3-FPM is quantitative determination of unchanged 3-FPM together with qualitative verification of a number of selected metabolites to verify consumption and rule out discharge.